Understanding History : and Other Essays. - Russell, Bertrand (Philosophical Library/Open Road, 2014)
Originally written in 1943 and published in 1957 by Philosophical Library, Inc, these vigorous essays from one of the most distinguished minds of our time reveal several facets of the English philosopher's thought. The title piece exposes the deadliness of the academic approach to the past, and shows how the reading of history can be a vivid intellectual pleasure. In "The Value of Free Thought," Russell once again proves himself a ruthless foe of stifling orthodoxy and a fearless champion of free thought, free action and free speech. Then in a series of articles on a subject near to his heart,